Security versus Threat – Interrelations - Wioletta Koper-Staszowska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2018)
The issue of interrelations between security and threat has a history as long as the history of mankind. Human beings since the beginning of times have always had needs of higher and lower importance, these needs sometimes collide with the needs and interests of others, thus creating a threat. Originally, the meaning of the term ‘security’ was limited only to the armed protection of territories against the enemies from neighboring countries. With time other layers of threat were recognized and determined. Nowadays, protection against external aggression is just one of many threats which must be dealt with to provide security to a state, other threats are related to economic, ecological, social or cultural aspects.